PEMBUKTIAN DALAM MENENTUKAN KERUGIAN KONSUMEN DALAM TRANSAKSI ELEKTRONIK - Tami Rusli (Universitas Bandar Lampung (UBL), 2019)
The development of e-commerce in Indonesia took place long before the Electronic Law waspassed, this e-commerce transaction itself would be predicted to continue to increase whichcould eventually lead to disputes between business actors and consumers. The problem in thisstudy is how to determine the proof of consumer losses in electronic transactions. Theapproach method used is a normative juridical approach method, secondary data sourcedfrom the study of literature and data analysis using qualitative analysis. The results of thestudy prove that to prove the existence of losses for consumers, of course, evidence is neededwhich can be used as evidence guidelines in standard agreements electronically.Conventionally proof is done in the form of print-outs or proof of writing with legalization.This can be done by adopting various provisions that contain the legal strength of electronicevidence as stipulated in the UNCITRAL Model Law On Electronic Commerce. Suggestionsneed to be immediately updated about the direction of the Indonesian Treaty Law inaccordance with Indonesia's national interests, so as to be able to participate in anincreasingly global world in the cyber era.